Transpecific polymorphisms in an inversion linked esterase locus in drosophila buzzatii - Gómez, G.A. (2003)
Nucleotide variation was studied in a 1.1 kb section of the coding region of an Esterase gene (Est-A) that maps in the center of the segments rearranged by polymorphic inversions in the cactophilic Drosophila buzzatii. We examine 30 homozygous second-chromosome lines differing in gene arrangement and three D. koepferae isofemale lines as outgroups. Our data show that Est-A is a highly polymorphic gene at both synonymous and replacement sites. Significant departures from homogeneity in the distribution of the ratio of silent polymorphism to divergence predicted by the neutral theory reveals a local excess of silent polymorphism. This is consistent with the presence of two apparent narrow peaks of elevated silent polymorphism surrounding nonconservative amino acid substitutions. These polymorphisms as well as others at synonymous and nonsynonymous sites are shared with D. koepferae. We suggest that the presence of shared nucleotide polymorphisms is probably due to interspecific gene flow and/or balancing selection acting on replacement variants and/or to a decreased probability of loss of ancestral polymorphisms caused by linkage to an adaptive inversion polymorphism. Recurrent mutation and persistence of neutral ancestral polymorphisms cannot, however, be ruled out. The analysis of the distribution of nucleotide variation among the three chromosomal arrangements sampled reveals that derived arrangements (J and JZ3) are less polymorphic than the ancestral ST, and that the widely distributed ST and J arrangements are genetically differentiated. However, a significant number of polymorphisms are shared between arrangements, suggesting frequent exchange either from gene conversion or from double crossovers in heterokaryotypes. Finally, our present results in combination with data of sequence variation at the breakpoints of inversion J suggest that this old gene arrangement has risen in frequency in relatively recent times.